Development of Bioadhesive Microspheres for Oral Bioavailability Enhancement of Berberine Hydrochloride - Ye Zhang; Hongming Liu (International Journal of Polymer Science)
The objective of this study was to innovatively prepare chitosan-coated alginate/gelatin BBH loaded microspheres and evaluate their pharmaceutical characteristics and pharmacokinetics. The bioadhesive microspheres were prepared using an emulsification technique. Three batches of microspheres were formed and their stability was evaluated. BBH loaded microspheres were almost spherical with shallow elevation on surfaces. The mean particle size of microspheres was 368.2 μm, drug loading was 3.59±0.01%, and in situ bioadhesion percentage was 91.23%±8.2% and they achieved a sustained release with 71.29% for 8 hours in vitro. Pharmacokinetic studies in rats indicated that the bioavailability of BBH microspheres was enhanced about 1.5-fold as compared with commercial tablets. BBH microspheres exhibited a sustained-release profile over 48 h. Thus, chitosan-coated alginate/gelatin BBH loaded microspheres which combined the advantages of alginate/gelatin microspheres and chitosan may be used as a sustained delivery system for BBH to treat duodenal and benign gastric ulcers.